Christ, the Logos of Creation: An Essay in Analogical Metaphysics by John R. Betz, Emmaus Academic, Steubenville Ohio, 2023, 556 pages, hardcover, £49,32, ISBN: 978-1-945125-13-3 - Bentz, Jan (New blackfriars, 2025)
Christ, the Logos of Creation: An Essay in Analogical Metaphysics by John R. Betz, Emmaus Academic, Steubenville Ohio, 2023, 556 pages, hardcover, £49,32, ISBN: 978-1-945125-13-3 - Volume 106 Issue 1